Cone Beam Computed Tomography Evaluation of the Artery in the Lateral Wall of the Maxillary Sinus: Retrospective Analysis of 602 Sinuses. Issue 4 (August 2018) - Rostetter, Claudio; Hungerbühler, Alex; Blumer, Michael; Rücker, Martin; Wagner, Maximilian; Stadlinger, Bernd; Lübbers, Heinz-Theo
Abstract : Purpose: This retrospective study evaluates the location of the arteries in the maxillary sinus, particularly in the middle portion, using cone beam computed tomography (CBCT) scans that can detect the lateral arteries with high reliability. Methods: In this retrospective study, 2 experienced independent examiners evaluated 602 sinuses on CBCT scans. Discussion: No significant correlation was found between the location of arteries and the patient's age, sex, or dentition. In 92.0% (P ⩽ 0.001) of the sinuses, at least 1 arterial branch was detectable. Conclusion: Based on the CBCT scans, we found that a very high proportion of patients have the maxillary artery in their lateral sinus wall, which is important information for sinus augmentation or sinus surgery.